Teachers’ Views on Classroom Infrastructure Facilities in Special Education Integration Program in Primary School - Norwahidah Mihat; Mohd Hanafi Mohd Yassin; Mohd Mokhtar Tahar (Department of Special Education, 2019)
The main aim of the research is to ensure effective lesson and produce best impact in classroom by providing conducive and comfortable condition. The objective of this research is to obtain Special Education Teachers’ views regarding the Special Education Integration Program (PPKI) in primary school in Seremban, Negeri Sembilan. This research was conducted quantitatively based on Maslow’s hierarch needs theory. A random sampling method is used in gathering the research data involving 137 special education primary school teachers. The research instrument is an adaptation from the questionnaire of the special education infrastructure needs in Malaysia. The data were analyzed descriptively. The findings showed that the level of special education classroom facilities special education teachers’ views is at moderate level. The research concludes that improvements in infrastructure facilities need to be done to meet the UDL model requirements for the convenience of special education students.